Escola em Aristóteles: instituição de formação cultural e ético-política - Bastos, Luciene Maria (2014)
This thesis, developed in the research line Fundamentals of Educational Processes, interrogates the nature, direction, idea, the real soul of the man’s training school, issue that must precede and illuminate the discussion, the understanding and the action, the theory and the práksis in teaching, learning, in the teacher training and in the public policies. School and training, concerned primarily with technical professionalisation, the development of competencies, the logic of the economy and marketing deplete the human’s constitution in the human being, of its ethical dimension. This work thinks, with the philosophy, conceptions and specific practices of the school as an organization at the service of economic interests dominate in the current form of society. The effort to understand the meaning and the nature of education and the school, inseparable from collective life, the culture and the training, as well as of new horizons of thought and action, follows the Ancient Greece, especially in the V and IV centuries BC. Emphasizes the grandeur and the rigor of the Corpus Aristotelicum, particularly the Nicomachean Ethics and the Politics, its discussion of the práksis, of areté, excellence, moral virtue, of eudaimonía, happiness, the political nature of the human being, vital to think about what the education is, the training and the school. The text is structured in three chapters. The first seeks to understand the Greek roots of our conception of man, of politics, of collective life and education, which ones are essential to thinking and rebuild the school. The Greeks bequeath us the political reason, the primacy of life in common, joined by philía ties, friendship, confirmed by seeing from de other’s eye. The citizen feels part of a whole community, to participate effectively in public life, assuming responsibility for what belongs to all of us and guiding their choices and actions for the pursuit of the common good. This way of life only builds through education as paideía, cultural and ethical-politics training, seeing the areté, excellent way of life. The second chapter discusses the man as being the logos, the phrónesis as an act of thinking and deliberating about the customs, the laws and the values, guiding the decisions and choices towards excellence. The purpose of human life supposes the subsumption of desires and interests to the right, and the search for the good life, enlivened by the justice, for freedom, for the common good. Form the man, the citizen who truly participates in the collective life, always seeking the common good is not develop skills and competencies, enable him to perform functions and carry out tasks, unlike, is shaping, upgrade their autonomy and freedom, seeking the imposition of ethical life, morally virtuous. The third chapter examines human life as inseparable from the skholé, leisure, creative freedom, not pressed by the needs. This time is the ontological foundation of the school as an institution of formation of excellent man, autonomous and free, committed to the good life, the ethical life; and he does not let to reduce himself to a training and staging center for the work, giving contents supposedly useful to the world production.